From The History Of Construction Of Water Facilities In Kashkadarya Oasis (Eurasian Journal of History, Geography and Economics, 2023)
In the article, the agricultural traditions of the Kashkadarya oasis, which is considered the southern region of Uzbekistan, the emergence and development of ancient water structures, the characteristics of water structures in different periods, ideologies and the influence of political systems by the human society, the types of water structures are described. issues such as views regarding their changes and their importance and scope are still being used today.